5(t-3)-3(2-t)=

Simple and best practice solution for 5(t-3)-3(2-t)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(t-3)-3(2-t)= equation:


Simplifying
5(t + -3) + -3(2 + -1t) = 0

Reorder the terms:
5(-3 + t) + -3(2 + -1t) = 0
(-3 * 5 + t * 5) + -3(2 + -1t) = 0
(-15 + 5t) + -3(2 + -1t) = 0
-15 + 5t + (2 * -3 + -1t * -3) = 0
-15 + 5t + (-6 + 3t) = 0

Reorder the terms:
-15 + -6 + 5t + 3t = 0

Combine like terms: -15 + -6 = -21
-21 + 5t + 3t = 0

Combine like terms: 5t + 3t = 8t
-21 + 8t = 0

Solving
-21 + 8t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + 8t = 0 + 21

Combine like terms: -21 + 21 = 0
0 + 8t = 0 + 21
8t = 0 + 21

Combine like terms: 0 + 21 = 21
8t = 21

Divide each side by '8'.
t = 2.625

Simplifying
t = 2.625

See similar equations:

| 15x-7x=8x | | 1.3+5(x-0.1)=-1.2-3x | | 2x+x^2+2x^2+x= | | (3x-45)= | | (2z)+(2z)+(3z-3)+(3z-3)=74 | | 2x+15-33=x | | 17+3x=125 | | (a-b+c)(-5)+61= | | 5m-20=0 | | 3(4q-1)-2(3q+4)= | | N+10=-10-6n-1 | | X=83-0.15x | | D=d-1-(3d+4)+(5-4d)-(7d+5)+5 | | 3(x-5)-8=-4(x-2) | | 10x+3=3-4x | | (a-b+c)(-5)-61a= | | 5x+4=4x-13 | | f(x)=2x^2+20x+58 | | 6(y-1)=x+4 | | 5x+3-2x+17=2 | | x+x+x+5x= | | -8p+1=2-9p | | y-12=2.5(x-3) | | x+4=6(y-1) | | A+7A-A= | | 25+15x=235 | | (5X-135)= | | X+0.15x=83 | | 3x+2(6-x)+5=37-9x | | 30+15x=235 | | -6-9b=3-6b | | x/4+26=40 |

Equations solver categories